Porcine reproductive and respiratory syndrome virus nonstructural protein 4 induces apoptosis dependent on its 3C-like serine protease activity. - Zhitao Ma (Public Library of Science (PLoS), 2013)
Porcine reproductive and respiratory syndrome (PRRS) is a highly contagious disease in pigs caused by PRRS virus (PRRSV). Although PRRSV infection-induced cell apoptosis has been established, the related viral protein is still unknown. Here, we reported that PRRSV nonstructural protein 4 (nsp4) was a critical apoptosis inducer. Nsp4 could activate caspase-3, -8, and -9. Using truncated constructs without different domains in nsp4, we demonstrated that the full-length of nsp4 structure was required for its apoptosis-inducing activity. Furthermore, using site-directed mutagenesis to inactivate the 3C-like serine protease activity of nsp4, we showed that nsp4-induced apoptosis was dependent on its serine protease activity. The ability of nsp4 to induce apoptosis was significantly impaired by His39, Asp64, and Ser118 mutations, suggesting that His39, Asp64, and Ser118 were essential for nsp4 to trigger apoptosis. In conclusion, our present work showed that PRRSV nsp4 could induce apoptosis in host cells and might be partially responsible for the apoptosis induced by PRRSV infection. PRRSV 3C-like protease-mediated apoptosis represents the first report in the genus Arterivirus, family Arteriviridae.